Curricular and Pedagogical Aspects to Be Taken into Account for Curriculum Redesign and Development in a Master’s Program in Higher Education - Sindy Susana Alvarado-Herrera; German Eduardo González-Sandoval; Yarina Paniagua-Cortés (Revista Electrónica Educare)
This project addresses the publications of a group of renowned authors in order to highlight important aspects to be considered by the Education Master’s Program in Higher Education and Teaching of the National University of Costa Rica as part of its improvement strategies in teacher education, taking into account the most recent tendencies related to internationalization, mobility, accreditation, academic management and shared leadership in higher education. The paper aims to portray a proposal that fulfills the needs of the Costa Rican master’s programs in higher education and teaching by approaching this country’s reality in terms of what the programs offer. It is a bibliographic research paper, which sources have been published for no longer than 10 years and are truly groundbreaking in regard to the graduate program trends that guide this production. Moreover, as part of the contextualization needed, all master’s degrees in higher education and teaching offered in the country are taken into consideration. As a result of this research, it can be concluded that these programs are pertinent, especially the one offered by the National University of Costa Rica, and it is evident that disseminating the program’s highlights and achievements through processes that respond to quality criteria for graduate programs truly needs to be encouraged.